The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1111/j.1365-2184.1986.tb00731.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth Characteristics of Human Melanoma Multicellular Spheroids In Liquid‐Overlay Culture: Comparisons With the Parent Tumour Xenografts

Abstract: The growth characteristics of multicellular spheroids, derived from human melanoma xenografts and cultivated in liquid-overlay culture, were studied and compared with those of the parent tumours. Six of the seven melanomas investigated formed spheroids, which grew exponentially up to a volume of 1-2 x lo7 pm3 (a diameter of 270-340 pm) before the growth rate tapered off. The morphology of the spheroids varied considerably among the melanomas; some spheroids grew as densely packed, spherical structures of cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 28 publications
0
34
0
Order By: Relevance
“…Yuhas & Li (1978) have studied the growth in liquid-overlay culture of spheroids initiated from seven murine solid tumours and concluded that the growth fraction was the major determinant of the volumetric growth rate. Previous studies in our laboratory of spheroids initiated from human melanoma xenografts have also shown that differences in volume-doubling time among different spheroid cultures are mainly a consequence of different growth fractions (Rofstad et al, 1986a). One possible explanation of the present observations may therefore be that the culture conditions in vitro through adequate nutrients stimulated cell proliferation, whereby the growth fraction as well as the fraction of clonogenic cells increased.…”
Section: Resultsmentioning
confidence: 45%
See 3 more Smart Citations
“…Yuhas & Li (1978) have studied the growth in liquid-overlay culture of spheroids initiated from seven murine solid tumours and concluded that the growth fraction was the major determinant of the volumetric growth rate. Previous studies in our laboratory of spheroids initiated from human melanoma xenografts have also shown that differences in volume-doubling time among different spheroid cultures are mainly a consequence of different growth fractions (Rofstad et al, 1986a). One possible explanation of the present observations may therefore be that the culture conditions in vitro through adequate nutrients stimulated cell proliferation, whereby the growth fraction as well as the fraction of clonogenic cells increased.…”
Section: Resultsmentioning
confidence: 45%
“…One possible explanation of the present observations may therefore be that the culture conditions in vitro through adequate nutrients stimulated cell proliferation, whereby the growth fraction as well as the fraction of clonogenic cells increased. However, there is evidence from studies of human melanoma xenografts that distinctly different stem-cell subpopulations may be predominant in tumours and in the corresponding spheroids (Rofstad et al, 1986a). Consequently, it cannot be excluded that the changes in plating efficiency and volumetric growth rate observed here were due to some stem-cell subpopulations being favoured by the growth conditions in vitro.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…Clonogenicity, Soft Agar, and Tumor Growth Assays-A clonogenicity assay was used to measure cell viability as a function of colony formation following anchorage-independent growth on SeaPlaque agarose-coated plates for up to 72 h (44). Briefly, IEC-18, ras3, ras4, and ras7 cells were trypsinized, and 500 cells were seeded onto 60-mm dishes coated with 2 ml of 1% (w/v) SeaPlaque agarose in MEM.…”
Section: Methodsmentioning
confidence: 99%